2011
DOI: 10.4103/0255-0857.90159
|View full text |Cite
|
Sign up to set email alerts
|

Association of platelet count and serological markers of dengue infection-importance of NS1 antigen

Abstract: Inclusion of NS1 in the diagnosis of dengue increases the detection rate significantly. In cases of fever, thrombocytopenia is more consistently found in dengue positive rather than dengue negative subjects. It correlates well when NS1 and IgM are detected simultaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
45
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 11 publications
21
45
1
2
Order By: Relevance
“…75(42.61%) dengue seropositive cases were detected to have thrombocytopenia in our study [ Table 3]. Soumy K et al [17] and Kulkarni RD et al [21] proved a significant association between thrombocytopenia and dengue infection. In the present study, leucopenia was detected in 69 (39.20%) seropositive cases [ Table 3].…”
Section: Seroepidemiology and Gender Related Differences In Laboratorsupporting
confidence: 55%
“…75(42.61%) dengue seropositive cases were detected to have thrombocytopenia in our study [ Table 3]. Soumy K et al [17] and Kulkarni RD et al [21] proved a significant association between thrombocytopenia and dengue infection. In the present study, leucopenia was detected in 69 (39.20%) seropositive cases [ Table 3].…”
Section: Seroepidemiology and Gender Related Differences In Laboratorsupporting
confidence: 55%
“…However almost half (81, 48.8%) patients from total 166 patients who came within 2 days of fever were tested positive for Dengue. This could be due to high sensitivity and specificity of Dengue NS 1 antigen ELISA test which was the sole test selected for patients presents early in acute stage of Dengue (Kulkarni et al, 2011;Peeling et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In rest of 32 positive cases both NS 1 antigen and Ig M antibody were detected. Various studies have indicated that NS 1 antigen helps in early detection and confirmation of diagnosis (Kulkarni et al, 2011;Datta et al, 2010;Krunal Mehta et al, 2016). When month wise trend was depicted on graph it reinforced the fact that surge in Dengue vector and so the rise in dengue cases occur in Monsoon and post monsoon season (WHO Dengue fever 2nd Edition 1997, Madhulika Mistry et al, 2015;Durani et al, 2014;Piyush tripathi et al, 2008 …”
Section: Resultsmentioning
confidence: 99%
“…However, this is not within the reach of peripheral and even most tertiary care laboratories (Peeling et al, 2010;Kulkarni et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The complications like DHF and DSS are usually attributed to this cross-reactivity in secondary infections (Kulkarni et al, 2011).…”
Section: Introductionmentioning
confidence: 99%